Contemporary communication systems using MATLAB - Proakis, John G. (Brooks/Cole, 2000)
Featuring a variety of applications that motivate students, this book serves as a companion or supplement to any of the comprehensive textbooks in communication systems. The book provides a variety of exercises that may be solved on the computer using MATLAB„µ (The authors assume that the student is familiar with the fundamentals of MATLAB). By design, the treatment of the various topics is brief. The authors provide the motivation and a short introduction to each topic, establish the necessary notation, and then illustrate the basic concepts by means of an example.